PolyAQG Framework: Auto-generating assessment questions - Tan, Tee Hean *; Teh, Phoey Lee *; Zaharin Yusoff, (2021)
Designing and setting assessment questions for examinations is always a necessary task for educators. In this article, we identify the research gaps in (semi-) automatically generating questions by evaluating all the available approaches developed thus far. We then propose a framework that puts together previous approaches and suggests ways to fill in their gaps. One hundred and thirteen pieces of literature relevant to question generation approaches have been reviewed and compared. For each of the approaches, the uniqueness of the techniques is explained. The PolyAQG Framework is presented with an explanation of how it would contribute to the solution of the problem, by improving the variety of the questions, increasing the total number of possible choices of question selections, as well as providing a better quality of questions. Apart from the framework, another novelty in this work is the innovative way a domain ontology is used to generate a wider variety of questions.